The factors influencing luminescent properties of ZnS:Mn obtained by the method of one-stage synthesis - Bacherikov, Yu.Yu.; Zhuk, A.G.; Optasyuk, S.V.; Okhrimenko, O.B.; Kardashov, K.D.; Kozitskiy, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Considered in this paper is the model that combines appearance of defects responsible for self-activated (SA) emission in ZnS with its piezoelectric properties. Being based on analysis of the luminescence spectrum, the authors demonstrate the influence of mechanical destruction, impact of ultrasound, microwave radiation and pulsed magnetic field on the emission efficiency for centers of luminescence connected with intrinsic defects in ZnS:Mn prepared using the method of self-propagating hightemperature synthesis (SHS). It has been shown that downsizing the ZnS:Mn crystals prepared according to the above method as well as more discrete differentiation of phases present in this material due to development and growth of inner boundaries and surface under external actions leads to quenched SA-photoluminescence with λ ~ 400–525 nm